Along-strike variation of structural style: Mansourabad Anticline in the Dezful Embayment, SW Iran - Afroogh, Abdolvahab; Shoghi, Jaber; Seraj, Mohammad; Mukherjee, Soumyajit; Azar, Javid Hassanzadeh (Results in Earth Sciences, 2024)
Understanding the governing factors that influence structural style and fault-related folding mechanisms is crucial in the Dezful Embayment, an area of ∼ 60,000 km2 which accounts for most of oil production from Iran. Such studies enable the subsurface kinematic modeling of structures and structural geological analysis of hydrocarbon traps. In this study, variations in geometry and folding mechanism along the strike of the Mansourabad anticline are studied through field data, 2D and 3D seismic lines interpretation and well data. The displacement-distance profile of the forelimb thrust fault indicates that the anticline is a fault propagation fold in its central and NW parts. In the SE part of the anticline, there is a north-verging detachment fold, which is opposite to the southward vergence at the NW part. Due to structural variations, the amount of slip along the NW-SE trending Behbahan Fault varies. This variation in structural style results from changes in slip along the Behbahan Fault's forelimb. This blind thrust, which trends NW-SE, extends along the entire length of the Mansourabad anticline. The variable thickness of the syn-folding sediments controlled the structural style of the anticline, which interacted with the migration of the Gachsaran Formation and the deformation of the competent rocks. •Geophysical data interpretation suggests that the Mansourabad anticline in the Dezful Embayment varies in structural style along its strike.•The Mansourabad Anticline is a fault propagation fold in its central and NW parts.